Internalized stigma related to COVID-19 and its psychosocial and mental health correlates: a multicentric health facility based observational study from Nepal - Shah, Bigya; Mahapatra, Ananya; Singh, Uday Narayan; Mishra, Vilok; Daha, Sunil Kumar; Pande, Rajan; Neupane, Madan Ratna; Banjade, Anita; Khatik, Chandra Bhal; K. C., Tej Bahadur; Mandal, Rajesh Kumar; Pokharel, Samjhana; et al. (Frontiers in Psychiatry, 2024)
The COVID-19 pandemic has led to physical and psychological complications and social consequences in the form of illness-related stigma. This study aimed 1) to assess the sociodemographic and clinical variable, as well as COVID-19 related knowledge and perception of persons admitted for COVID-19/Suspected COVID-19 in Nepal, 2) to determine their levels of COVID-19-related internalized stigma, depression, and anxiety symptoms, and 3) to evaluate the correlates of COVID-19-related internalized stigma.It was a cross-sectional exploratory study with a convenience sample of 395 participants (306 confirmed cases, 89 suspected cases) conducted between July-October 2020 in four health facilities in Madhesh and Lumbini provinces of Nepal. We used a semi-structured questionnaire to assess sociodemographic details, clinical information, COVID-19-related knowledge, perception, COVID-19-related internalized stigma , and the Hamilton Anxiety Depression Scale (HADS) in Nepali language. Descriptive statistics, correlation analyses, and linear regression analyses were performed. The level of statistical significance was considered at p<0.05.Around 23.3% of the patients had anxiety symptoms, 32.9% had depressive symptoms, and 20.3% had high COVID-19-related internalized stigma (mean ISMI score: 2.51-4.00). Linear regression analyses showed a significant positive association of COVID-19-related internalized stigma total score, with the following eight factors, i.e., no income in the past one month( p=0.013), below average socioeconomic status(p=0.004), anxiety symptoms (p=<0.001), depressive symptoms (p=<0.001), recent testing positive for COVID-19 (p=<0.001), involuntary admission (p=<0.001), prior experience of being in isolation and quarantine (p=0.045), and those who blame others for COVID-19 (p=0.025).COVID-19 survivors and suspects are vulnerable to symptoms of depression, anxiety, and COVID-19-related internalized stigma. For the first time from Nepal, our data suggests that COVID-19-related internalized stigma is associated with anxiety and depression symptoms, perceived below-average socioeconomic status, involuntary admission, prior experience of being in isolation and quarantine, recent COVID-19 positive report, self-blame, below-average socioeconomic status and no income in the past one month. Mitigating and preventing internalized stigma associated with a public health crisis such as COVID-19 is imperative by diagnosing and treating such mental health issues early and designing interventions and policies especially targeting vulnerable populations focusing on their economic background and sociocultural beliefs.